Constante retorno del objetivismo en la responsabilidad. Crítica desde aportes de moralistas y juristas escolásticos ante una concepción asumida de versari in re illicita = Constant Return of Objectivism in Responsibility. Criticism from Contributions of Scholastic Moralists and Jurists to an assumed Conception of versari in re illicita - Vargas Pinto, Tatiana (Cauriensia, 2024)
The easy attribution of effects from illicit conduct is well reflected in the usual objective understanding of versari in re illicita. The study shows how a series of inaccuracies from that meaning leads to maintaining an objective imputation that affirms responsibility (and liability) for results. Although similar objective canonical references are found, the assignment of chance is not true in the scholastic use. The context of development of the versari, the confusion about the idea of casus, as well as explanations from Thomistic sources, make it possible to contradict the traditional objective interpretation of the maxim. Instead, in the Thomistic scholasticism there is a necessary relationship between objective and subjective aspects from the versari as an imputation rule.